Physicochemical characterization of the fruits of the Unconventional Food Plants (UFP), snake gourd (Trichosanthes cucumerina) - Ana Carolina Xavier Pereira de Maria Fernandes; Luis Carlos Cunha Junior; Diogo Pedrosa Correa da Silva; André José de Campos; Cristiane Maria Ascari Morgado; Daniela Santana de Souza; Abadia dos Reis Nascimento (Brazilian Journal of Food Technology)
Abstract Unconventional food plants emerge in a context where people increasingly care about living healthier. Among these plants, the snake gourd (Trichosanthes cucumerina) of Asian origin and belongs to the Cucurbitaceae family, produces fruits that can reach more than 1 m in length. This study aimed to physiochemically characterize the fruits in different lengths and harvest times. The fruits were harvested with the following lengths: between 0.2-0.35 m, 0.45-0.6 m, and 0.7-0.85 m; and at the following times: 115 and 135 days after planting. The attributes evaluated were soluble solids, titratable acidity, vitamin C, firmness, pH, dry matter, antioxidant activity, and polyphenols. The fruits of meter okra with 0.2-0.35 m and 0.45-0.6 m presented better color characteristics, greener, brighter, and with greater saturation. In addition, they presented higher values of soluble solids and lower firmness. At 115 days after planting, the fruits showed higher values of vitamin C, better color, lower acidity, and higher soluble solids content. Thus, we conclude that the fruits should be harvested with a maximum of 0.6 m and up to 115 days after planting.